Phosphorylation of the insulin receptor kinase by phosphocreatine in combination with hydrogen peroxide: the structural basis of redox priming - Schmid, Elmar; Hotz-Wagenblatt, Agnes; Dröge, Wulf (The FASEB journal, 1999)
Signaling by insulin requires autophosphorylation of the insulin receptor kinase (IRK) at Tyr1158, Tyr1162, and Tyr1163. Earlier experiments with 32P‐γ‐ATP indicated that the nonphosphorylated IRK (IRK‐0P) is relatively inactive, and crystallographic data indicated that the ATP binding site of IRK‐0P is blocked by its activation loop.
Gesehen am 09.02.2021